Incidence and severity of competition injuries in Australian amateur taekwondo athletes: a two-year prospective study - Lystad, R. P.; Graham, P. L.; Bonello, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
There is a seeming paucity of prospective data on injury severity and risk factors for injury in Olympic-style taekwondo, particularly among amateur taekwondo athletes (Lystad et al., 2009). The main purposes of this study were to determine the injury incidence and severity in Australian amateur taekwondo athletes, and to investigate potential risk factors for injury in competition taekwondo. Methods: Data were collected prospectively at New South Wales (Australia) State Taekwondo Championships during 2010 and 2011 seasons. Injuries were diagnosed by tournament sports medicine personnel and recorded according to the Orchard Sports Injury Classification System, version 10. Injury severity was recorded by conducting post-tournament follow-up of injured athletes to determine the actual number of days lost from full participation. Injury incidence rates were calculated per 1,000 athlete-exposures (IIR_AE) and per 1,000 minutes of exposure (IIR_ME). All injury incidence rates, rate ratios and relative risks were computed with 95% confidence intervals (CIs) using standard methods. Results: The combined data revealed an overall IIR_AE of 59.93 (CI: 51.16, 69.77). The lower limb was found to be the most common injury location, the contusion to be the most common type of injury, and receiving a blow to be the most common mechanism of injury. One third of injuries were found to result in more than one week of lost or restricted participation. There was no significant difference between the genders. Children were found to have a significantly lower IIR_AE compared to their older age groups, and black belts to have a significantly higher IIR_AE compared to yellow belts. However, none of these differences were present after accounting for the duration of exposures (i.e. comparing IIR_ME). The proportion of upper limb injuries resulting in fractures was significantly higher than lower limb injuries resulting in fractures (relative risk: 9.90 [CI: 2.12, 46.20]). Discussion: Although significant differences in IIR_AE were detected within belt ranks and age groups, no significant differences could be demonstrated after accounting for the exposure-time. This highlights the importance of reporting injury incidence rates with the duration of exposures factored into the denominator. Contrary to what has previously been suggested, the current data indicated that as many as one third of injuries resulted in more than one week of restricted participation (Pieter, 2009). Relative to the lower limb a disproportionate number of upper limb injuries were found to result in fracture.